Pengaruh Beban Kerja Dan Gaya Kepemimpinan Birokratis Terhadap Kinerja Karyawan Pada UB Guest House - Juniar Sofyan Syah; Budi Wahono; Eris Dianawati (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract This study aims to examine the effect of workload and bureaucratic leadership style on the performance of UB Guest House employees. The theory that is used in this research is Workload Theory, Social Exchange Theory, and Bureaucratic Leadership. The researcher uses Social Exchange Theory to identify the relationship between employees and leaders. This research uses descriptive quantitative analysis method and statistical analysis method by implementing Multiple Regression Test. Based on the collected data, it shows a positive influence of workload and bureaucratic leadership style on employee performance either partially or simultaneously. Keywords : Workload, Bureaucratic Leadership Style, Employee Performance, UB Guest House